An Empirical Analysis on Cost Efficiency and Determinants of Commercial Banks in China - Li, Muzhou (2019)
Abstract During the period 2009-2014, under the influence of the Belt and Road Initiative, China’s new normal economy and the stock market turbulence, the cost efficiency of Chinese commercial banks is fluctuated greatly. In this study, the cost efficiency of 100 commercial banks operating in China was evaluated by using SFA method. The mean cost efficiency score ranges from 59.34% to 97.78%. Then, by employing the Tobit regression model to analyze factors of the cost efficiency. ROAA has a negative impact on the cost efficiency and bank size has no significant impact on the cost efficiency. Key words: the cost efficiency, China commercial banks, SFA method